Two Cysteines in Raf Kinase Inhibitor Protein Make Differential Contributions to Structural Dynamics In Vitro - Hyun Sang Cho; Mohammad Faysal Al Mazid; Eun-Young Lee; Md Abu Rayhan; Hyoun Sook Kim; Byung Il Lee; Hye Jin You (Molecules)
As a scaffolding protein, Raf kinase binding protein (RKIP) is involved in a variety of cellular pathways, including the Raf–MEK–ERK-cascade. It acts as a negative regulator by binding to its partners, making it an attractive target in the development of therapeutic strategies for cancer. Despite its structural stability as a monomer, RKIP may form a dimer, resulting in the switching of binding partners. It is still unclear how RKIP switches between monomeric and dimeric forms. Here, we identified the role of cysteine 133 in RKIP structural dynamics using recombinant human RKIP (rhRKIP) proteins purified from Escherichia coli BL21(DE3) cells. Mutation of alanine or serine instead of cysteine in RKIP proteins did not affect the biochemical characteristics, while dynamic light scattering and liquid chromatography (LC) quadrupole time-of-flight (Q-TOF) mass spectrometry (MS) suggested distinct peaks in solution, which were identified via LC–MS/MS analyses, and further clarified the role of cysteine in RKIP dimerization. rhRKIP dimer formation was abrogated by a 32-aa peptide mimicking the region between two RKIP proteins for dimerization. In addition, the 32-aa peptide and its short derivatives were investigated for effects on cancer cell viability. Taken together, our findings suggest that it may be possible to regulate RKIP function by controlling its dynamics with reducing agents, which could aid the targeting of cancer cells.